PENGARUH PEMAHAMAN WAJIB PAJAK, SANKSI PAJAK DAN TINGKAT KEPERCAYAAN PADA PEMERINTAH TERHADAP KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN (STUDI KASUS PADA WAJIB PAJAK DI DESA SAGA) - Priyanti, Ananda Dwi; Fitriyah (Jurnal Nusa Akuntansi, 2024)
This research aims to determine Taxpayer Understanding, Tax Sanctions, and the Level of Trust in the Government Regarding Taxpayer Compliance in Paying Land and Building Taxes. The research method used is a quantitative method with an associative approach. The population in the study was 6.312 land and building tax payers in Saga Village in 2023, with a sample size of 100 respondents calculated using the Slovin formula with an error rate of 10%. The sampling technique uses convenience sampling technique. The data analysis method uses the validity test, reliability test, classical assumption test, linear regression test, R2 coefficient of determination test, T test, and F test using SPPS software version 27. The results of this study show that partially the variable Taxpayer Understanding and Sanctions Taxes have an effect on taxpayer compliance in paying land and building taxes, while the level of trust in the government has no effect on taxpayer compliance in paying land and building taxes. Simultaneously Taxpayer Understanding, Tax Sanctions, and Level of Trust in the Government simultaneously influence Taxpayer Compliance in Paying Land and Building Taxes.